2021
DOI: 10.3168/jds.2020-19888
|View full text |Cite
|
Sign up to set email alerts
|

Changes in bacterial community and expression of genes involved in intestinal innate immunity in the jejunum of newborn lambs during the first 24 hours of life

Abstract: The newborn gut undergoes rapid colonization by commensal microorganisms and possible exposure to pathogens. The contribution of colostrum intake to host protection is well known; however, limited research exists on the intestinal innate immunity corresponding to colostrum intake during the passive immune transfer period in newborn ruminants. The aim of this study was to investigate the changes in bacterial community and expression of genes encoding toll-like receptors (TLR), mucins (MUC), antimicrobial peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Provision of adequate immunoglobulin (Ig) mass to calves is essential for survival, health, and future productivity ( 16 ). Colostrum components also participate in regulating the development of the intestinal mucosal immune barrier in newborn lambs during the passive immune transfer period ( 17 ). However, failed passive transfer (FPT) is a common problem in newborn calves ( 18 ), causing increased mortality, diarrhea, respiratory diseases, and septicemia in young calves ( 19 21 ), and even decreasing their first lactation milk yield ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Provision of adequate immunoglobulin (Ig) mass to calves is essential for survival, health, and future productivity ( 16 ). Colostrum components also participate in regulating the development of the intestinal mucosal immune barrier in newborn lambs during the passive immune transfer period ( 17 ). However, failed passive transfer (FPT) is a common problem in newborn calves ( 18 ), causing increased mortality, diarrhea, respiratory diseases, and septicemia in young calves ( 19 21 ), and even decreasing their first lactation milk yield ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…The TLRs are associated with microbial colonization. The expression of TLR2, TLR4, and TLR5 in the jejunum of newborn ruminants was significantly correlated with the relative abundance of bacteria, which play an important role in intestinal defense during the passive immune transfer period ( Zhu et al, 2021 ). Correlation analysis indicated that TLR4 expression was negatively correlated with the relative abundance of Bradyrhizobium and Rudaea.…”
Section: Discussionmentioning
confidence: 99%
“…Pinocytosis of enterocytes also have a role in that maternal antibody absorbtion by the newborn [37]. PIT is a complex of reactions by acting together Toll-Like Receptors, Mucins, antimicrobial peptides, and Claudins in intestinal defense during the PIT in newborn lambs [38]. On the other hand, Fc receptor mediated pathways are key mechanism in IgG metabolism [39].…”
Section: Introductionmentioning
confidence: 99%